Stereoselective Ring-Opening Deacetonation Polymerization of Racemic 2,2,5-Trimethyl-1,3-dioxolan-4-one by Using Homosalen–Aluminum Complexes: A Novel Approach to Isotactic Poly(rac-lactic acid) - Sakai, Kazuho; Yagi, Yusuke; Nomura, Nobuyoshi (Synlett, 2023)
A novel approach is reported for the synthesis of the highly isotactic poly(racemic lactic acid) [P(rac-LAA)] from racemic 2,2,5-trimethyl-1,3-dioxolan-4-one by using achiral homosalen–Al catalysts. The polymerization proceeded through two steps: stereoselective ring-opening and deacetonation. The effects of substituents on the homosalen–Al catalyst were clarified regarding the polymerization rates and polydispersity of the obtained P(rac-LAA), but were still unclear regarding the iso-stereoselectivity. The P(rac-LAA) obtained by using an isopropyl-substituted homosalen–Al catalyst showed the highest isotacticity (Pm = 0.96), a moderate number-average molecular weight (Mn = 6,200), and broad polydispersity (PDI = 2.20). Differential scanning calorimetric measurements indicated that the polymer was semicrystalline with a melting temperature of 156 °C.
Keywords: ring-opening polymerization; deacetonation; lactic acid; polylactic acid; polymerization catalyst; homosalen, isotactic